Lawmaking at the WHO: Amendments to the international health regulations and a new pandemic treaty after COVID-19 - Pedro A. Villarreal (Stiftung Wissenschaft und Politik (SWP), 2023)
Two concurrent lawmaking processes are currently underway at the World Health Organization (WHO) that could lead to a new pandemic treaty and to amendments to the International Health Regulations (IHR) of 2005. However, two major questions must first be addressed. Firstly, how can global health equity be fostered in the future worldwide distribution of medical supplies during a pandemic? And secondly, how can incentives be put in place so that information on disease outbreaks is exchanged more rapidly and transparently?
Keywords: 320; World Health Organization (WHO); International Health Regulations (IHR); COVID-19; COVAX initiative